Carbon nanotube hybrid particle and preparation method and application thereof

By introducing poly TTTSi-based ionic liquid into the carbon nanotube and polymer composite materials, the carbon nanotube hybrid particles are constructed, and the dispersion problem caused by carbon nanotube agglomeration is solved, efficient heterogeneous nucleation and functionalization of the material are achieved, and foamed materials with excellent performance are obtained.

CN119684681APending Publication Date: 2025-03-25TAIZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411858377.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

In the prior art, when using unmodified carbon nanotubes to prepare composite materials, carbon nanotubes are prone to agglomeration, resulting in uneven dispersion, affecting the heterogeneous nucleation, functionalization and flame retardant properties of the material, and at the same time, the processing technology is complex.

Method used

By synthesizing polyTTTSi-based ionic liquid (TTTSi-[VBTMA]X) with carbon nanotubes through π-π and π-cation interactions, the synergistic effect of polyionic liquid and carbon nanotubes is achieved.

Benefits of technology

On the basis of maintaining the integrity of the carbon nanotube structure, it realizes its effective recombination with polyionic liquid, improves CO2 adsorption capacity and heterophase nucleation efficiency, improves the cell structure, enhances the tensile strength and foam density of polypropylene, and obtains a lightweight and high-strength foaming material with excellent comprehensive performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119684681A_ABST
    Figure CN119684681A_ABST
Patent Text Reader

Abstract

The invention discloses a carbon nanotube hybrid particle as well as a preparation method and application thereof, the carbon nanotube hybrid particle is constructed by taking tetravinyl cyclotetrasiloxane (TTTSi) as a core to synthesize a poly TTTSi-based ionic liquid, and then through the interaction of pi-pi and pi-cations between the ionic liquid and a carbon nanotube, the carbon nanotube hybrid particle is constructed. The carbon nano tube hybrid particles prepared by the method are an adsorbent of carbon dioxide (CO2) and a heterogeneous nucleating agent of PP microcellular foaming, and the polyion liquid and the carbon nano tube are both compatible with CO2 and can generate a synergistic effect. The foam density of PP can be reduced by 28.2% and the tensile strength can be improved by 38.6% by adding 2% (by mass) of the carbon nanotube hybrid particles synthesized by the invention, which are obviously better than those of a commercially available foam regulator.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to carbon nanotube hybrid particles and a preparation method and application thereof, belonging to the technical field of composite materials. Background Art

[0002] Carbon nanotubes (CNTs) are one-dimensional carbon nanoparticles with a unique structure. They have good application prospects in polymer foaming, functionalization and flame retardancy. At present, the main way to use CNTs for polymer microporous foaming is to blend them with polymers to prepare composite materials and then implement foaming. In the foaming process of composite materials, the dispersion of CNTs plays a decisive role in the heterogeneous nucleation, functionalization and flame retardancy of the materials. Unmodified carbon nanotubes are easy to agglomerate due to van der Waals forces. Although they can be effectively dispersed after chemical grafting modification, there is a problem of destroying the complete structure and functionalization of carbon nanotubes, and the processing technology is complicated. Summary of the invention

[0003] In view of the above problems existing in the prior art, the present invention aims to provide a carbon nanotube hybrid particle and its preparation method and application. The present invention uses tetravinylcyclotetrasiloxane (TTTSi) as a core to synthesize a poly-TTTSi-based ionic liquid (TTTSi-[VBTMA]X), utilizes the π-π and π-cation interactions between the ionic liquid and CNTs to construct CNTs hybrid particles, and realizes the synergistic effect of the poly-ionic liquid and carbon nanotubes.

[0004] In the application research of functional ionic liquids in composite materials, it was found that macromolecular ionic liquids adsorb CO 2 It has strong ability and is introduced into polypropylene (PP) plastic as an additive to achieve CO 2 High saturation absorption in PP.

[0005] On the basis of maintaining the integrity of the CNTs structure, the CNTs hybrid particles were effectively compounded with polyionic liquids to obtain CNTs hybrid particles, which were then used in PP supercritical CO 2 Microporous foaming can achieve CO 2 The local enrichment on the surface of CNTs hybrid particles improves the heterogeneous nucleation efficiency and improves the pore structure. On the other hand, both the microporous structure and carbon nanotubes have a reinforcing and toughening effect on PP. The two are expected to produce a synergistic effect, which is conducive to obtaining a lightweight and high-strength foaming material with excellent comprehensive performance. The CNTs hybrid particles have high stability and structural controllability, which can achieve the improvement of the comprehensive performance of PP microporous foaming materials.

[0006] The specific technical solution is:

[0007] A carbon nanotube hybrid particle, the structure of which is shown in formula (IV):

[0008]

[0009] The method for preparing carbon nanotube hybrid particles comprises the following steps:

[0010] First, the compound shown in formula (I) is reacted with a quaternary ammonium salt ionic liquid (II) containing a double bond to generate a poly-TTTSi-based ionic liquid (III);

[0011] Then, the carbon nanotube hybrid particles as shown in formula (IV) are constructed by using the π-π and π-cation interactions between the polyTTTSi-based ionic liquid and the carbon nanotubes;

[0012] The compound shown in formula (I) is tetravinylcyclotetrasiloxane TTTSi containing a double bond, and its structure is shown in formula (I):

[0013]

[0014] The compound shown in formula (II) is a benzyl vinyl trimethyl salt [VBTMA]X containing a double bond, and its structure is shown in formula (II):

[0015]

[0016] In formula (II), X - Chloride - , tetrafluoroborate BF 4 - PF6 6 - or bis(trifluoromethanesulfonyl)imide TF 2 N - ;

[0017] The structure of the polyTTTSi-based ionic liquid is shown in formula (III):

[0018]

[0019] The specific method is:

[0020] (1) dissolving tetravinylcyclotetrasiloxane TTTSi and double-bonded benzylvinyl trimethyl salt [VBTMA]X in solvent I, stirring with a magnetic stirrer at 20-30°C until the white powder is completely dissolved, adding a catalyst, and heating to 90-95°C for reaction for 16-24 hours;

[0021] The molar ratio of tetravinylcyclotetrasiloxane TTTSi and benzylvinyltrimethyl salt [VBTMA]X in step (1) is 1:0.5-3.

[0022] The solvent I in step (1) is N,N-dimethylformamide (DMF); the volume amount of the solvent I is 10-30 mL / mmol based on the amount of tetravinylcyclotetrasiloxane.

[0023] The catalyst in step (1) is one of recrystallized azobisisobutyronitrile AIBN and azobisisoheptanenitrile ABVN; the amount of the catalyst used is 0.05-0.2 g / mmol based on the amount of tetravinylcyclotetrasiloxane.

[0024] (2) After the reaction is completed, the reaction solution is poured into solvent II to obtain a mixed solution a, the solid product precipitated in the mixed solution a is filtered and extracted with solvent III, and the filter cake is vacuum dried to obtain a polyTTTSi-based ionic liquid represented by formula III, namely TTTSi-[VBTMA]X;

[0025] The solvent II in step (2) is one of ethanol and methanol; the volume amount of the solvent II is 50-100 mL / mmol based on the amount of tetravinylcyclotetrasiloxane;

[0026] The solvent III in step (2) is diethyl ether; the volume amount of the solvent III is 50-100 mL / mmol based on the amount of tetravinylcyclotetrasiloxane.

[0027] (3) dissolving the polyTTTSi-based ionic liquid and the hydroxylated multi-walled carbon nanotubes in solvent IV, dispersing them by ultrasound, adding a reducing agent, and reacting them at 95-100° C. with magnetic stirring for 16-24 hours to obtain a reaction solution b;

[0028] The solvent IV in step (3) is one of propylene carbonate and deionized water; the volume amount of the solvent IV is 50-150 mL / g based on the mass of the carbon nanotubes.

[0029] The reducing agent in step (3) is hydrazine hydrate; the volume amount of hydrazine hydrate used is 0.5-2mL / g based on the mass of the carbon nanotubes.

[0030] (4) The reaction solution b is decompressed, distilled, and the filter cake is vacuum dried to obtain the carbon nanotube hybrid particles represented by formula (IV).

[0031] The carbon nanotube hybrid particles are used as raw materials for preparing polypropylene microporous foaming materials. The carbon nanotube hybrid particles prepared by the present invention are carbon dioxide (CO 2 ) adsorbent and heterogeneous nucleating agent for PP microporous foaming, polyionic liquids and carbon nanotubes are both 2 Adding 2% (mass fraction) of the carbon nanotube hybrid particles synthesized by the present invention can reduce the foam density of PP by 28.2% and increase the tensile strength by 38.6%, which is significantly better than the commercially available cell regulators.

[0032] By adopting the above technology, compared with the prior art, the present invention has the following beneficial effects:

[0033] (1) The carbon nanotube hybrid particles prepared by the present invention are a kind of CO 2 adsorbent and heterogeneous nucleating agent for PP microporous foaming, polyionic liquid and carbon nanotubes are both 2 The addition of 2% (mass fraction) of the carbon nanotube hybrid particles synthesized by the present invention can reduce the foam density of PP by 28.2% and increase the tensile strength by 38.6%, which is significantly better than the commercially available cell regulators.

[0034] (2) The carbon nanotube hybrid particles prepared by the present invention can be used as an additive for polypropylene microporous foaming materials, which is simple to operate and easy to control. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 This is the SEM image of the PP foam material in Example 1;

[0036] Figure 2 It is the SEM image of the PP foam material in the comparative example. DETAILED DESCRIPTION

[0037] The technical solution of the present invention is further described below with reference to embodiments, but the protection scope of the present invention is not limited thereto.

[0038] Embodiment 1:

[0039] Weigh 0.01 mol (3.4466 g) of tetravinylcyclotetrasiloxane (TTTSi) and 1 mol (32.1290 g) of benzylvinyltrimethyl hexafluorophosphate ([VBTMA] [PF 6 ]) and 200 ml of N,N-dimethylformamide (DMF) were added to a 500 ml single-necked flask, and magnetic stirring was performed until the white powder was completely dissolved. Then, 1 g of recrystallized azobisisobutyronitrile (AIBN) was added, and the temperature was raised to 90°C for 24 hours. After the reaction was completed, the reaction solution was poured into a methanol solution to precipitate a white precipitate, which was filtered and extracted with ether. The product was dried in vacuo at 80°C for 24 hours to obtain 30.5950 g of the polyTTTSi-based ionic liquid (TTTSi-[VBTMA][PF 6 ]), with a yield of 86%. In a 500 ml single-necked flask, 3 g of hydroxylated multi-walled carbon nanotubes and 300 ml of deionized water were added, and the dispersion was achieved by ultrasound. Then, 3 ml of hydrazine hydrate and 6 g of TTTSi-[VBTMA][PF 6], and reacted with magnetic stirring at 95-100°C for 24 hours. After the reaction, the solvent was removed by centrifugation, and the product was washed three times with deionized water. The product was vacuum dried at 80°C for 12 hours to obtain 8.595 g of carbon nanotube hybrid particles (CNT / TTTSi-[VBTMA][PF 6 ]), yield 95.5%.

[0040] Weigh 1 g of carbon nanotube hybrid particles and 49 g of PP and prepare a sample using a micro extruder and a micro injection machine at 200 °C. The foam density is measured to be 0.28 g / cm 3 , the tensile strength is 25.67MPa, and the SEM image of the foamed material is shown in Figure 1 shown.

[0041] Embodiment 2:

[0042] Weigh 0.01 mol (3.4466 g) of tetravinylcyclotetrasiloxane (TTTSi) and 2 mol (52.62 g) of benzylvinyltrimethyltetrafluoroborate ([VBTMA] [BF 4 ]) and 200 ml of N,N-dimethylformamide (DMF) were added to a 500 ml single-necked flask, and magnetic stirring was performed until the white powder was completely dissolved. Then, 1 g of recrystallized azobisisoheptanenitrile (ABVN) was added, and the temperature was raised to 90°C for 24 hours. After the reaction, the reaction solution was poured into a methanol solution to precipitate a white precipitate, which was filtered and extracted with ether. The product was dried in vacuo at 80°C for 24 hours to obtain 43.6198 g of the polyTTTSi-based ionic liquid (TTTSi-[VBTMA][BF 4 ]), with a yield of 77.8%. In a 500 ml single-necked flask, 3 g of hydroxylated multi-walled carbon nanotubes and 300 ml of deionized water were added, and the dispersion was achieved by ultrasound. Then, 3 ml of hydrazine hydrate and 6 g of TTTSi-[VBTMA][BF 4 ], and reacted with magnetic stirring at 95-100°C for 24 hours. After the reaction, the solvent was removed by centrifugation, and the product was washed three times with deionized water. The product was vacuum dried at 80°C for 12 hours to obtain 8.82 g of carbon nanotube hybrid particles (CNT / TTTSi-[VBTMA][BF 4 ]), yield 98%.

[0043] Weigh 1 g of carbon nanotube hybrid particles (CNT / TTTSi-[VBTMA][BF 4 ]) and 49 g PP were used to prepare the sample strips at 200°C using a micro extruder and a micro injection machine, and the foam density was measured to be 0.32 g / cm 3 , the tensile strength is 23.25MPa.

[0044] Embodiment 3:

[0045] Weigh 0.01 mol (3.4466 g) of tetravinylcyclotetrasiloxane (TTTSi) and 1 mol (42.8760 g) of benzylvinyltrimethylbis(trifluoromethanesulfonyl)imide ([VBTMA] [TF 2 N]) and 200 ml of N,N-dimethylformamide (DMF) were added to a 500 ml single-necked flask, and magnetic stirring was performed until the white powder was completely dissolved. Then, 1 g of recrystallized azobisisobutyronitrile (AIBN) was added, and the temperature was raised to 90 ° C for 24 hours. After the reaction, the reaction solution was poured into a methanol solution to precipitate a white precipitate, which was filtered and extracted with ether, and dried in a vacuum at 80 ° C for 24 hours to obtain 41.3198 g of the product polyTTTSi-based ionic liquid (TTTSi-[VBTMA][TF 2 In a 500 ml single-necked flask, 3 g of hydroxylated multi-walled carbon nanotubes and 300 ml of deionized water were added, and the dispersion was achieved by ultrasound. Then, 3 ml of hydrazine hydrate and 6 g of TTTSi-[VBTMA][TF 2 N], and reacted with magnetic stirring at 95-100°C for 24 hours. After the reaction, the solvent was removed by centrifugation, and the product was washed three times with deionized water. The product was vacuum dried at 80°C for 12 hours to obtain 8.568 g of carbon nanotube hybrid particles (CNT / TTTSi-[VBTMA][TF 2 N]), yield 95.2%.

[0046] Weigh 1 g of carbon nanotube hybrid particles (CNT / TTTSi-[VBTMA][TF 2 N]) and 49 g PP were used to prepare the sample strips at 200 ° C using a micro extruder and a micro injection machine. The foam density was measured to be 0.33 g / cm 3 , the tensile strength is 23.67MPa.

[0047] Comparative Example:

[0048] Weigh 1 g of commercially available cell regulator (PA798) and 49 g of commercially available PP and prepare a sample strip using a micro extruder and a micro injection machine at 200°C. The foam density is 0.39 g / cm 3 , the tensile strength is 18.52MPa, and the SEM image of PP foam material is shown in Figure 2 shown.

[0049] Table 1

[0050]

[0051] The test results of the comparative examples and embodiments are shown in Table 1.

Claims

1. A carbon nanotube hybrid particle, characterized in that: Its structure is shown in formula (IV):

2. The method for preparing carbon nanotube hybrid particles according to claim 1, characterized in that: The following steps are involved: First, the compound shown in formula (I) is reacted with a quaternary ammonium salt ionic liquid (II) containing a double bond to generate a poly-TTTSi-based ionic liquid (III); Then, the carbon nanotube hybrid particles as shown in formula (IV) are constructed by using the π-π and π-cation interactions between the polyTTTSi-based ionic liquid and the carbon nanotubes; The compound shown in formula (I) is tetravinylcyclotetrasiloxane TTTSi containing a double bond, and its structure is shown in formula (I): The compound shown in formula (II) is a benzyl vinyl trimethyl salt [VBTMA]X containing a double bond, and its structure is shown in formula (II): In formula (II), X - Chloride - 、Tetrafluoroborate BF4 - , hexafluorophosphate PF6 - or bis(trifluoromethanesulfonyl)imide TF2N - ; The structure of the polyTTTSi-based ionic liquid is shown in formula (III):

3. The method for preparing carbon nanotube hybrid particles according to claim 2, characterized in that: The specific method is: (1) dissolving tetravinylcyclotetrasiloxane TTTSi and double-bonded benzylvinyl trimethyl salt [VBTMA]X in solvent I, stirring with a magnetic stirrer at 20-30°C until the white powder is completely dissolved, adding a catalyst, and heating to 90-95°C for reaction for 16-24 hours; (2) After the reaction is completed, the reaction solution is poured into solvent II to obtain a mixed solution a, the solid product precipitated in the mixed solution a is filtered and extracted with solvent III, and the filter cake is vacuum dried to obtain a polyTTTSi-based ionic liquid represented by formula III, namely TTTSi-[VBTMA]X; (3) dissolving the polyTTTSi-based ionic liquid and the hydroxylated multi-walled carbon nanotubes in solvent IV, dispersing them by ultrasound, adding a reducing agent, and reacting them at 95-100° C. with magnetic stirring for 16-24 hours to obtain a reaction solution b; (4) The reaction solution b is decompressed, distilled, and the filter cake is vacuum dried to obtain the carbon nanotube hybrid particles represented by formula (IV).

4. The method for preparing carbon nanotube hybrid particles according to claim 3, characterized in that: The molar ratio of tetravinylcyclotetrasiloxane TTTSi and benzylvinyltrimethyl salt [VBTMA]X in step (1) is 1:0.5-3.

5. The method for preparing carbon nanotube hybrid particles according to claim 3, characterized in that: The solvent I in step (1) is N,N-dimethylformamide (DMF); the volume amount of the solvent I is 10-30 mL / mmol based on the amount of tetravinylcyclotetrasiloxane.

6. The method for preparing carbon nanotube hybrid particles according to claim 3, characterized in that: The catalyst in step (1) is one of recrystallized azobisisobutyronitrile AIBN and azobisisoheptanenitrile ABVN; the amount of the catalyst used is 0.05-0.2 g / mmol based on the amount of tetravinylcyclotetrasiloxane.

7. The method for preparing carbon nanotube hybrid particles according to claim 3, characterized in that: The solvent II in step (2) is one of ethanol and methanol; the volume amount of the solvent II is 50-100 mL / mmol based on the amount of tetravinylcyclotetrasiloxane; The solvent III in step (2) is diethyl ether; the volume amount of the solvent III is 50-100 mL / mmol based on the amount of tetravinylcyclotetrasiloxane.

8. The method for preparing carbon nanotube hybrid particles according to claim 3, characterized in that: The solvent IV in step (3) is one of propylene carbonate and deionized water; the volume amount of the solvent IV is 50-150 mL / g based on the mass of the carbon nanotubes.

9. The method for preparing carbon nanotube hybrid particles according to claim 3, characterized in that: The reducing agent in step (3) is hydrazine hydrate; the volume amount of hydrazine hydrate used is 0.5-2 mL / g based on the mass of the carbon nanotubes.

10. The use of the carbon nanotube hybrid particles according to claim 1, characterized in that: As raw material for preparing polypropylene microporous foam material.